The Relationship Of Dental And Mouth Disease With The Quality Of Life Of Children In Talawaan Minahasa Sub-District - Youla Karamoy (Faculty of Public Health, Andalas University, 2017)
Dental and mouth health play an important role to get good health. Mouth disease cause pain, suffering, social deprivation and psychologi-cal barriers, which are highly detrimental to both individuals and society including the children. School age children is one of the groups that are vulnerable to dental and mouth health problems. The study aim to know the relationship of dental and mouth disease with the child’s quality of life. The study design was cross-sectional conducted in North Minahasa subdistrict with sample taken by convenience sampling. Data analysis of univariate and bivariat analysis. Results of univariate analysis obtained average dental caries with PUFA index was 0.77 and the Calculus Index (CI) was 0.75. The average of PUFA index of subjects whose parents work in nonformal higher (0.88) than subjects whose parents work in a formal (0.76). Bivariat analysis obtained significant corelation between dental caries and the child’s quality of life index PUFA (r =-0.418, p = 0.000) and Calculus Index (r =-0.158, p = 0,091). The better children’s dental health status the better the child’s quality of life. It is therefore advised to care for dental and mouth health in children so that can increase the quality of life .